Individual rights and state duties, bioethical considerations around the debate over emergency contraception in Chile - Villarroel Soto, Raúl (Acta Bioethica, 2007)
This essay tries to show a moral, social and politically relevant debate in Chile: the controversy about emergency contraception and the decision of government authorities to authorize state health care services to distribute the drug commonly known as "the day after pill". Different views of analysis are studied to reach, finally, a bioethical reflection of the problem considering a re-examination of the classical principles perspective, to point out some of its analytical inadequacies and, for this reason, to rethink the problem under a human rights perspective